Analysis of External Risks of Cholera Importation to the Territory of Primorsky Krai by Different Types of Transport - Zh. Yu. Khunkheeva; L. V. Mironova; V. A. Seleznev; M. A. Chebotar; A. I. Kovalenko; I. V. Kuznetsova; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика, 2021)
Relevance. The risk of developing complications of an epidemiological nature for especially dangerous infections is determined by the possibility of importing an infection from disadvantaged countries, which depends on many factors, including the migration activity.Aim. To analyze the external risks of cholera importation into Primorsky Krai by various modes of transport.Materials and methods. Data of the Federal Service for Surveillance on Consumer Rights Protection and Far Eastern territorial department Federal Service for Surveillance on Consumer Rights Protection and Human Wellbeing by railway transport was used. The analysis of the incidence of cholera in the world was carried out according to the WHO, the Reference Center for Monitoring Cholera in the Russian Federation, the Internet resource ProMED-mail.Results and discussion. During the analyzed period (2015–2018), 311,435 vehicles (automobile transport – 87.4%, sea transport – 7.7%, air transport – 4.3%, railway transport – 0.6%) and more than 5 million people arrived in Primorsky Krai from abroad. Analysis of passenger flows by all modes of transport showed that Asian destinations dominate.Conclusion. Evaluation of the epidemiological situation of cholera in the Southeast Asian countries does not rule out the risk of cholera importation into Primorsky Krai, given the high intensity of migratory activity. No conflict of interest to declare.